EFEKTIVITAS PEMBELAJARAN PETA KONSEP DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI KESEBANGUNAN DAN KEKONGRUENAN DITINJAU DARI KREATIVITAS - NAINGGOLAN, JONNER; PASARIBU, HUMISAR BTPJ (Jurnal Ilmu Pendidikan Indonesia, 2021)
The purpose of this study was to determine whether the mathematics learning outcomes on the congruence and congruence material taught by concept maps were better than students taught by conventional methods. The variables in this study were two independent variables (1) learning methods, and (2) students' creativity and one dependent variable, namely mathematics learning outcomes. The sample in this study were students of class IX B and IX E SMP Negeri 2 Abepura Jayapura. Data collection methods used in this study are: documentation, questionnaires and test methods. Questionnaires and tests used to retrieve data in research before use were tested for validity and reliability. The processed data is data that is normally distributed and homogeneous. The results of the study showed that students' mathematics learning outcomes on the similarity and congruence material taught with concept maps were better than those taught by conventional methods. Mathematics learning outcomes of students on similarity and congruence materials that have high creativity are better than moderate creativity. The mathematics learning outcomes of students on similarity and congruence materials that have moderate creativity are better than low creativity